To find the correct linear equation, we can break down the information provided.
Let:
- \( a \) be Tony's current age.
- Since Andrea is 6 years younger than Tony, Andrea's current age can be expressed as \( a - 6 \).
In two years:
- Tony's age will be \( a + 2 \).
- Andrea's age will be \( (a - 6) + 2 = a - 4 \).
According to the problem, in two years, Tony will be three times as old as Andrea. This gives us the equation:
\[ a + 2 = 3(a - 4) \]
Now we can simplify this equation:
-
Expand the right side: \[ a + 2 = 3a - 12 \]
-
Rearrange it to isolate terms involving \( a \): \[ 2 + 12 = 3a - a \] \[ 14 = 2a \] \[ a = 7 \]
To find the linear equation from the options given that corresponds to our derived equation, we see: \[ a + 2 = 3(a - 4) \]
None of the options are in exactly this form. However, we can match it with:
- \( a - 6 \):
The closest match is:
Answer: \( a + 2 = 3(a - 6 + 2) \)
This option can be simplified and checks out with the setup as it ultimately leads to the same relationship we derived.